Incidence of arthropods in dried fish products - Mohanasundaram, M., Kalaimani, N., Unnikrishnan Nair, T.S. and (Fishery Technology, 2021)
Arthropods have been recorded from various types of insect infested dried fish products stored in the laboratory. They have been identified as Suidesia nesbetti Hughes (Acaridae) infesting dried anchovies and dried mussel, Dermestes ater Dermestidae coleoptera) attacking wet cured sardines and smoked catfish and Stegobium panicium infesting smoked catfish and dried mussel. Incidences of Stegobium panicium in dry fish products and Suidesia nesbetti in dried mussel has been recorded for the first time.